Insight into contraction dynamics of microwave plasmas for CO2 conversion from plasma chemistry modelling. (29th October 2020) - Viegas, P; Vialetto, L; Wolf, A J; Peeters, F J J; Groen, P W C; Righart, T W H; Bongers, W A; van de Sanden, M C M; Diomede, P
Abstract: This work addresses plasma chemistry in the core of a vortex-stabilized microwave discharge for CO2 conversion numerically, focusing on the pressure-dependent contraction dynamics of this plasma. A zero-dimensional model is presented for experimental conditions in a pressure range between 60 and 300 mbar and a temperature range between 3000 and 6500 K. Monte Carlo flux (MCF) simulations, which describe electron kinetics, are self-consistently coupled to the plasma chemistry model. The simulation results show that an increase in pressure is accompanied by a transition in neutral composition in the plasma core: from a significant amount of CO2 and O2 at low pressures to a O/CO/C mixture at high pressures, the composition being determined mostly by thermal equilibrium and by transport processes. The change of temperature and composition with pressure lead to higher ionisation coefficient and more atomic ion composition in the plasma core. These changes result in an increase in ionisation degree in the plasma core from 10 −5 to 10 −4 . These factors are shown to be fundamental to drive contraction in the CO2 microwave discharge.